BERNAMA opens more chances for IPT students - New Sarawak, Tribune (New Sarawak Tribune, 2012)
KUALA LUMPUR: The Malaysian National News Agency (BERNAMA) yesterday signed a memorandum of understanding (MoU) with seven public and five private institutions of higher learning (IPT) to accept more IPT students to undergo industrial training.